"This rhythm does not please me": women protest war in Dunya Mikhail's poetry - Al-Athari, Lamees (Kansas State University, 2008)
In her collection of poems The War Works Hard (2005), Iraqi-American poet Dunya Mikhail presents her readers with unembellished insight into the Iraqi war from a woman's perspective. This perspective is rarely voiced in Iraqi war literature which is dominated by male writers concerned with men's heroism at the battle front and boundless patriotism. At the same time, these male authors rarely depict Iraqi women's experiences of war beyond the battle grounds. Even when women are present in such literature, they often share their men's point of view on war and voice only their acceptance of it. Mikhail, however, contemplates a counter narrative to this stereotypical female role by presenting women who protest war and the destruction it causes. Her poems portray mothers, lovers, sisters and daughters who protest war's brutality and injustice. Some of the women in Mikhail's poems protest war by directly or indirectly criticizing its institutions and condemning the leaders who promote it. While other women in her work find that their protest lies in their de-fragmentation of the destruction and loss caused by war, thus refusing its power over them and their loved ones. Yet, the most important form of women's protest of war in Mikhail's work is recollection. Through the recollection of their fragmented memories and lives, Mikhail's women manage to survive and find a spark of optimism in the darkness that war has unleashed. Their survival and their ability to re-establish their lives apart from war and the presence of men constitutes a powerful and dramatic protest of war's control over their lives.
Keywords: Dunya Mikhail; Arab-American; Women in war; Iraqi poet; Iraq; Iraqi women; Literature, American (0591); Literature, English (0593); Women's Studies (0453)